2012
DOI: 10.1080/14763141.2011.637128
|View full text |Cite
|
Sign up to set email alerts
|

Does student learning style affect performance on different formats of biomechanics examinations?

Abstract: Students' learning style preferences have been widely adapted into teaching and learning environments. The purpose of this study was to investigate the relationship between self-reported and assessed learning style preferences (visual, auditory, reading/writing, kinesthetic: VARK) on performance in different types of multiple-choice examinations (T1: text only format and T2: visual format) given in an introductory biomechanics class. Students who enrolled in three biomechanics classes at a state university wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…Such acknowledgements are also consistent with self-determination theory (Ten Cate et al, 2011), as their engagement in more practical and career-oriented activities would be presumably underpinned by their motivation to develop their professional identities as future sports scientists or physiotherapists. These student perceptions were consistent with the significant positive associations between student perceptions of relevance of biomechanics to their careers and learning gains (Hsieh & Knudson, 2008;Hsieh, Mache, & Knudson, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…Such acknowledgements are also consistent with self-determination theory (Ten Cate et al, 2011), as their engagement in more practical and career-oriented activities would be presumably underpinned by their motivation to develop their professional identities as future sports scientists or physiotherapists. These student perceptions were consistent with the significant positive associations between student perceptions of relevance of biomechanics to their careers and learning gains (Hsieh & Knudson, 2008;Hsieh, Mache, & Knudson, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…Student learning style preferences (i.e., visual, aural, read/write, kinesthetic) can be measured using the VARK questionnaire (Fleming and Mills, ). Students who are assessed in the same format as their preferred learning style may perform better (Hsieh et al, ). Undergraduate chiropractic students (years 1–3) have previously been reported to have kinesthetic preferences (Whillier et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that students who favoured abstract thinking outperformed those who preferred concrete thinking in the science disciplines (Davies, Rutledge & Davies, 1997), and that reflective students were better in problem solving than active students (Hur & Kim, 2007). Despite this, many more studies disapproved the correlation between learning styles and academic performance (Demirkan & Demirbaş, 2010;Fleming et al, 2011;Gurpinar et al, 2010;Hsieh, Mache, & Knudson, 2012;Wilkinson, Boohan, & Stevenson, 2014). As for the relation between motivation and learning styles, studies have shown that certain styles were positively correlated with L2 motivation, such as visual style (Al-Shehri, 2009) and auditory style (Kim, 2009), while kinesthetic style was found to be negatively correlated with L2 motivation (Kim & Kim, 2011).…”
Section: Introductionmentioning
confidence: 99%